Analisis Kemampuan Pemecahan Masalah Matematik Dan Keaktifan Siswa Dalam Pembelajaran Matematika Pada Siswa SMA di Kabupaten Bandung Barat - Fitria Ambarwati Rasid; Ela Parida (Journal on Education, 2019)
This research originated from a preliminary study conducted at one of the schools in West Bandung High School regarding the importance of problem solving skills and student learning activeness. This study aims to analyze the problem solving abilities and student learning activeness in mathematics learning with the subject of class XII research. This study uses a qualitative descriptive method, according to Sugiyono (2013: 1) that qualitative research on its rights is a research method used to examine scientific circumstances. In accordance with research studies that have been revealed that mathematical problem solving abilities can be said to be low on several indicators of problem solving abilities, including understanding problems, solving problems according to plan and making mathematical models, solving problems, and checking answers. While the learning activeness ability of students can be dikatan still lacking in their learning activeness in paying attention, cooperating, expressing opinions, giving opportunities, and helping to solve problems